Comprehensive phenotyping of erythropoiesis in human bone marrow: Evaluation of normal and ineffective erythropoiesis. Issue 9 (3rd June 2021) - Yan, Hongxia; Ali, Abdullah; Blanc, Lionel; Narla, Anupama; Lane, Joseph M.; Gao, Erjing; Papoin, Julien; Hale, John; Hillyer, Christopher D.; Taylor, Naomi; Gallagher, Patrick G.; Raza, Azra; et al.
Abstract: Identification of stage‐specific erythroid cells is critical for studies of normal and disordered human erythropoiesis. While immunophenotypic strategies have previously been developed to identify cells at each stage of terminal erythroid differentiation, erythroid progenitors are currently defined very broadly. Refined strategies to identify and characterize BFU‐E and CFU‐E subsets are critically needed. To address this unmet need, a flow cytometry‐based technique was developed that combines the established surface markers CD34 and CD36 with CD117, CD71, and CD105. This combination allowed for the separation of erythroid progenitor cells into four discrete populations along a continuum of progressive maturation, with increasing cell size and decreasing nuclear/cytoplasmic ratio, proliferative capacity and stem cell factor responsiveness. This strategy was validated in uncultured, primary erythroid cells isolated from bone marrow of healthy individuals. Functional colony assays of these progenitor populations revealed enrichment of BFU‐E only in the earliest population, transitioning to cells yielding BFU‐E and CFU‐E, then CFU‐E only. Utilizing CD34/CD105 and GPA/CD105 profiles, all four progenitor stages and all five stages of terminal erythroid differentiation could be identified. Applying this immunophenotyping strategy to primary bone marrow cells from patients with myelodysplastic syndrome, identified defects in erythroid progenitors and in terminal erythroid differentiation. This novel immunophenotyping technique will be a valuable tool for studies of normal and perturbed human erythropoiesis. It will allow for the discovery of stage‐specific molecular and functional insights into normal erythropoiesis as well as for identification and characterization of stage‐specific defects in inherited and acquired disorders of erythropoiesis.